2020
DOI: 10.1037/dhe0000109
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating social-class identity: The persistence of working-class African American women doctoral students.

Abstract: Scholars have argued that there is a silence related to social class status in educational literature. Consequently, the purpose of this phenomenological study was to develop an understanding of the educational experiences of working-class African American women doctoral students at predominantly White institutions and what factors influence their doctoral persistence. Black feminist thought and the social class worldview model informed the conceptualization of the study. Ten doctoral students completed indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…Importantly, though, some multiply marginalized people develop adaptive coping strategies that can attenuate the impact of intersecting systems of oppression. For example, working-class virtues like self-efficacy and resiliency can support Black women navigating predominantly White systems (Crumb et al, 2020). In other cases, marginalized educational attainment may be protective, as in one study in which Black adults with a college education reported experiencing more discrimination than those with a high school education (Pew Research Center, 2019a), which researchers speculated may be the result of college-educated Blacks more likely working in predominantly White environments.…”
Section: Social Class and Classismmentioning
confidence: 99%
“…Importantly, though, some multiply marginalized people develop adaptive coping strategies that can attenuate the impact of intersecting systems of oppression. For example, working-class virtues like self-efficacy and resiliency can support Black women navigating predominantly White systems (Crumb et al, 2020). In other cases, marginalized educational attainment may be protective, as in one study in which Black adults with a college education reported experiencing more discrimination than those with a high school education (Pew Research Center, 2019a), which researchers speculated may be the result of college-educated Blacks more likely working in predominantly White environments.…”
Section: Social Class and Classismmentioning
confidence: 99%
“…There is research on graduate students of color, in general (e.g., Brunsma, Embrick, and Shin 2017; Curtis-Boles, Chupina, and Okubo 2020; Gay 2004; Hubain et al 2016; Noy and Ray 2012; Truong, Museus, and McGuire 2016), as well as literature specific to the experiences of graduate students who are Black (e.g., Allen and Joseph 2018; Barker 2016; Blockett et al 2016; Gooden, Devereaux, and Hulse 2020; Johnson-Bailey et al 2008), Latinx (e.g., Gildersleeve et al 2011; Ramirez 2017), Indigenous (Alejandro, Fong, and De La Rosa 2020; Shotton 2018), and Asian (e.g., Mayuzumi et al 2007). Racialized experience intersects with other dimensions of identity and oppression, including gender (e.g., Allen and Joseph 2018; Noy and Ray 2012; Squire et al 2018), sexuality (e.g., Means et al 2017), and class (Crumb et al 2020; Ramirez 2017). These studies overwhelmingly share similar and overlapping findings; thus, here, we collate findings from these studies.…”
Section: Bipoc Graduate Students In the United Statesmentioning
confidence: 99%
“…The “doctoral student advisor is a key stakeholder and gatekeeper for a student’s success during academic study and degree completion” (Blockett et al 2016:97). Loni Crumb et al’s (2020:221) study of working-class Black women graduate students finds that supervisors who “were responsive to students’ academic needs, personal wellness, research interests, and professional development contributed to their persistence.” While student persistence and expeditious completion of graduate school is correlated to various factors (including a strong academic self-concept and a sense of belonging), effective mentoring by the supervisor is “ the most important factor in achieving end goals such as degree attainment” (Brunsma et al 2017:6, emphasis in original). Supervisors play an essential role in providing guidance to students, including helping students develop their research and gain opportunities to present conference papers and co-author publications, and providing support in relation to funding and professional development (Blockett et al 2016:103).…”
Section: Experiences Of Canadian Bipoc Graduate Students As Researchersmentioning
confidence: 99%
“…This literature explores the shared experiences of graduate students of colour (e.g., Brunsma, Embrick, and Shin 2017;Curtis-Boles, Chupina, and Okubo 2020;Gay 2004;Hubain et al 2016;Noy and Ray 2012;Truong, Museus, and McGuire 2016), as well as literature on the specific experiences of graduate students who are Black (e.g., Allen and Joseph 2018;Barker 2016;Blockett et al 2016;Johnson-Bailey et al 2008), Latinx (e.g., Gildersleeve et al 2011;Ramirez, 2017), Indigenous (Alejandro, Fong, and De La Rosa 2020; Shotton 2018) and Asian (e.g., Mayuzumi et al 2007). Some of this literature examines how racialized experiences intersect with other dimensions of identity and oppression, including gender (e.g., Allen and Joseph 2018;Noy and Ray 2012;Squire et al 2018), sexuality (e.g., Means et al 2017) and class (Crumb et al 2020;Ramirez 2017).…”
Section: Classroom Experiences Of Bipoc Graduate Student In the Unite...mentioning
confidence: 99%